2016
DOI: 10.1126/science.aah3398
|View full text |Cite
|
Sign up to set email alerts
|

High-quality graphene via microwave reduction of solution-exfoliated graphene oxide

Abstract: Efficient exfoliation of graphite in solutions to obtain high-quality graphene flakes is desirable for printable electronics, catalysis, energy storage, and composites. Graphite oxide with large lateral dimensions has an exfoliation yield of ~100%, but it has not been possible to completely remove the oxygen functional groups so that the reduced form of graphene oxide (GO; reduced form: rGO) remains a highly disordered material. Here we report a simple, rapid method to reduce GO into pristine graphene using 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
431
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 746 publications
(456 citation statements)
references
References 57 publications
(71 reference statements)
18
431
0
7
Order By: Relevance
“…[27][28][29][30] Direct solid-state exfoliation by microwave and thermal shock has also been applied. [31][32][33][34][35] Typical gravimetric capacitance (≈250 F g −1 ) of such structures is still less than the theoretical value of 550 F g −1 due to the strong overlapping/aggregation of graphene layers via π-π aromatic interactions, thus leading to reduced accessibility of the interlayer spacing. [36][37][38][39] Considerable efforts have been devoted to minimize the aggregation.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[27][28][29][30] Direct solid-state exfoliation by microwave and thermal shock has also been applied. [31][32][33][34][35] Typical gravimetric capacitance (≈250 F g −1 ) of such structures is still less than the theoretical value of 550 F g −1 due to the strong overlapping/aggregation of graphene layers via π-π aromatic interactions, thus leading to reduced accessibility of the interlayer spacing. [36][37][38][39] Considerable efforts have been devoted to minimize the aggregation.…”
Section: Introductionmentioning
confidence: 94%
“…[1] Those are ideal for fast energy storage and delivery, e.g., for smart power grids and hybrid electric vehicles. [2] However, their energy density (3-5 Wh kg −1 ) is relatively low, compared with the traditional batteries (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) Wh kg −1 ). In order to boost their performance, efforts have been devoted to increase the specific capacitance of the electrode material, both in terms of the power and the energy densities.…”
Section: Introductionmentioning
confidence: 99%
“…With the addition of graphene, there would have an avalanche-like deoxygenation reaction under MW irradiation to reduce GO for synthesizing graphene ( Figure 5). Based on this conclusion, Voiry et al [52] lightly reduced GO by thermal annealing before exposure to microwaves, and this resulted in conductive GO, which could absorb microwaves effectively and led rapid heating and effective reduction of the GO. Park et al [100] fabricated high-quality graphene nanosheets (GNSs) by solid-state microwave irradiation of pretreated GNSs, and a hydrogen atmosphere was introduced to improve the quality of graphene products.…”
Section: Microwave Reductionmentioning
confidence: 99%
“…In the same principle, GO with moderate degree of reduction was subjected to microwave heating, leading to lowered content of oxygen functional groups and effectively repaired graphene structure. [51,52] Utilization of high energy photoirradiance was also shown to be an effective and energy-efficient way to repair defective RGO structures. [53,54] It has been demonstrated that through significantly lowered structural defects, such highly reduced GO (HRGO) products helped bring about significantly enhanced functional properties for chemical energy storage devices such as metal-ion batteries and supercapacitors (SC), when good crystallinity and associated high electric/ thermal conductivity are essential, as is summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Due to abundant hydrophilic group, graphene oxide can be used as biomolecular carriers for drug and gene delivery in biomedical field [12]. Now, the preparation of graphene commonly used physical and chemical methods: micro-mechanical stripping [9], liquid exfoliation [13,14], axial cutting carbon nanotube [15], chemical vapor deposition (CVD) [16,17], crystal epitaxial growth [18] and oxidation-reduction method [19].…”
Section: Graphenementioning
confidence: 99%